Join our team, change the world: edibility, producibility and food futures in cultured meat company recruitment videos. (1st January 2022) - Stephens, Neil
ABSTRACT: Cultured meat is a novel technology that uses tissue engineering to expand cells taken from animals to grow muscle for consumption as food. Those supporting the technology anticipate it could radically disrupt livestock farming with, they propose, significant benefits for the environment, human health, and animal wellbeing. This paper examines the emergence of this sector through the prism of one of the leading companies – Memphis Meats – in particular focusing upon their online recruitment activity in online videos. Founded in 2015, by 2020 they had announced investment of over $160 m to build a pilot-plant and recruit staff to bring cultured meat closer to commercialization. This paper argues the company's recruitment videos work to enact what I term "producibility", a concept aligned to existing work on "edibility", that emphasizes the process of becoming that foodstuff (included novel foodstuffs) undergo. I deploy existing theoretical work on multiple categories of futures – big/little, individual/institutional/field – to analyze Memphis Meats' online recruitment activity. I argue that, by entangling science and food futures, the company's videos work to assert the status and politics of cultured meat, render it producible and edible, and articulate a novel and transformative food-professional identity: the cultured meat producer.